Corrigendum to "The effectiveness of realistic mathematics education to enhance elementary students' learning outcomes and motivation" - Jesi Alexander Alim; Sri Retno Asih; Zetra Hainul Putra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
In the original published version of this article, the authors inadvertently omitted the Acknowledgement section. We sincerely apologize for this oversight and any confusion it may have caused. The updated PDF versions of the article reflect the necessary corrections, including the addition of the Acknowledgement section. Acknowledgement The authors are grateful to RISTEKDIKTI and LPPM Universitas Riau for funding this study under the DRTPM research grant of Fundamental scheme with the research grant number 20743/UN19.5.1.3/AL.04/2024.